2008
DOI: 10.1089/rej.2007.0587
|View full text |Cite
|
Sign up to set email alerts
|

Elastin Haploinsufficiency Induces Alternative Aging Processes in the Aorta

Abstract: Elastin, the main component of elastic fibers, is synthesized only in early life and provides the blood vessels with their elastic properties. With aging, elastin is progressively degraded, leading to arterial enlargement, stiffening, and dysfunction. Also, elastin is a key regulator of vascular smooth muscle cell proliferation and migration during development since heterozygous mutations in its gene (Eln) are responsible for a severe obstructive vascular disease, supravalvular aortic stenosis, isolated or ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
68
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 43 publications
7
68
0
1
Order By: Relevance
“…Vessels were carefully cleaned of adipose tissue, cannulated, and mounted onto a pressure arteriograph, placed onto a microscope with video monitoring. Mechanistic study was performed, as previously described 26, 27, 28. Circumferential wall stress (representative of all forces that are circumferentially applied on each small portion of the vessel wall) and incremental elastic modulus (Einc) (representative of wall stiffness) were calculated from the inner and outer diameters at transluminal pressures ranging from 0 to 175 mm Hg, according to the formulas given by Gibbons and Shadwick 29…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessels were carefully cleaned of adipose tissue, cannulated, and mounted onto a pressure arteriograph, placed onto a microscope with video monitoring. Mechanistic study was performed, as previously described 26, 27, 28. Circumferential wall stress (representative of all forces that are circumferentially applied on each small portion of the vessel wall) and incremental elastic modulus (Einc) (representative of wall stiffness) were calculated from the inner and outer diameters at transluminal pressures ranging from 0 to 175 mm Hg, according to the formulas given by Gibbons and Shadwick 29…”
Section: Methodsmentioning
confidence: 99%
“…Responses to PE are presented as the percentage decrease in inner diameter (ID), compared with the control diameter at 75 mm Hg before PE application: PE‐induced contraction (%)=100×(ID control −ID PE )/ID control . Responses to Ach are presented as the percentage restoration of the ID after PE‐induced constriction: Ach‐induced vasodilation (%)=100×(ID Ach+PE −ID PE )/(ID control −ID PE ) 27, 28…”
Section: Methodsmentioning
confidence: 99%
“…The elastin gene is the best-explored gene of the WBS region and it has been demonstrated that haploinsufficiency as well as heterozygous point mutations cause SVAS [29 -34, 170]. Heterozygous knock out mice of the Eln gene display high blood pressure, constriction of arteries and rigid arterial walls [170].…”
Section: The Single Copy Gene Part Of the Wbs Regionmentioning
confidence: 99%
“…Interestingly, Eln +/-mice are protected from vascular remodeling following carotid artery ligation in the ipsilateral vessel while enhanced remodeling occurs in the contralateral artery (88), suggesting that elastin haploinsufficiency may differentially affect ligation-mediated and flow-mediated injury responses. Eln +/-mice show the same CV remodeling response in the renal artery clipping model of adult hypertension as do wild-type animals (89) but are protected from the age-related vessel wall thickening observed in wild-type animals (90). Further clinical studies are needed to determine whether patients with WBS are also protected from age-related vascular changes.…”
Section: Mechanisms Of Obstructive Vascular Disease In Wbsmentioning
confidence: 99%